Cerebro–cerebellar crosstalk in motor and cognitive domains. Issue 3 (March 2016) - Molinari, M.
Abstract : Relations between cerebral cortex and cerebellum have been addressed for more than a century, nevertheless, our knowledge of the cerebellar contribution to cerebral processing is far from complete. Cerebro–cerebellar anatomic connectivity is known to be organized in discrete «parallel circuits» organized such that cerebellar regions that receive input from a given cortical area, relay output back to the same cerebral area. Cerebello–cerebral physiologic interactions in the motor domain have been largely addressed and it is now well established that motor cortex excitability can be modulated by cerebellar output, and Cerebellar Brain Inhibition (CBI) is a well-known phenomenon. Recently developed high density EEG methods allow to address cerebro–cerebellar neurophysiologic interactions with a large-scale network approach. Coupling of cortical and cerebellar activity in a variety of motor and non-motor tasks is a well-known phenomenon and cortical activity changes have been observed after cerebellar lesion and more recently after cerebellar transcranial direct current cerebellar stimulation. Overall, coupling mechanisms between cortical and cerebellar activity can be considered bidirectional and cerebral cortex network changes in patients with focal cerebellar lesion may provide insight on the nature of cerebro–cerebellar interactions.